Democratic Republic of the Congo : First Review Under the Three-Year Arrangement Under the Extended Credit Facility and Financing Assurances Review-Staff Report; Staff Supplement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Congo, Democratic Republic of the Democratic Republic of the Congo. (IMF Staff Country Reports; Country Report ;, 2010)
Congo's economic program aims to enhance macroeconomic stability and advance reforms to bolster economic management and improve the supply response of the economy. Progress in implementing the program has been affected negatively by the continuation of conflict. Fiscal policy aims at reducing government recourse to central bank financing. Structural reforms in revenue mobilization and public financial management (PFM) are critical for achieving the fiscal policy objectives. Pressing ahead with structural reforms is required for higher economic growth. Executive Directors suggest adoption of the Lending into Arrears Policy.